How Marine Megabenthos Fauna Responds to River Discharge and Artificial Flood in Large River Estuary - Debin Sun; Qinglu Fu; Jiao Wang; Linlin Chen; Jing Chen; Yilin Wang; Baoquan Li (Ecology and Evolution)
ABSTRACT Estuaries are ecologically sensitive areas influenced by river regulation. Knowledge of how marine megabenthos responds to river regulation and artificial flooding events remains limited. The study aims to provide a comprehensive understanding of the impacts of river regulation on marine megabenthic fauna. The oceanographic investigations were conducted at the Yellow River Estuary and its adjacent area during three distinct periods of river discharge, that is, spring low‐flow (IA), summer low‐flow (IB), and artificial flood (IC) periods. Samples of megabenthos and 14 mainly environmental parameters were investigated during different periods. The comprehensive indices of biodiversity (C‐diversity), phylogeny (C‐phyl), and stability (C‐stability) were synthesized from 24 basic indices to characterize the overall traits of megabenthos faunas. All 210 species were collected during three periods, belonging to 16 classes and 51 orders. The typical estuarine communities were mainly distributed in the key area within 30 km of the estuary during the low‐flow periods. The estuarine community presented with low biodiversity (C‐diversity = 0.15) but high stability (C‐stability = 0.64) during the IA period, followed by an increase in biodiversity during the IB period (C‐diversity = 0.35, C‐phyl = 0.69). The community underwent dramatic changes during the IC period, which bifurcated into distinct northern and southern groups. The northern community maintained high biodiversity and homeostasis (C‐stability = 0.60), whereas the southern stability decreased sharply (0.11). On the whole, the artificial flood reshaped the geographical distribution of megabenthic fauna in the estuarine area within 20 days, mainly as a result of the dramatic changes in seawater salinity and nutrient structure caused by flow pulse. An eco‐friendly discharge management of the Yellow River is needed to mitigate the impact.